La secularización en el contexto sociocultural latinoamericano (2018)
The proposal of the paper raises questions about the understanding of secularization as a new cultural scenario in which religious discourses reside. In this sense, the framework of the commemoration of the 50th anniversary of the Document of Medellín is explored, an approach to the concept of secularization, which includes the different ways of understanding the religious in postmodernity. Hence, these new understandings can help to contextualize contemporary theological reflection in a dialogue with the social sciences.